Advanced cancer is also a heart failure syndrome: a hypothesis. Issue 3 (18th March 2021) - Anker, Markus S.; Sanz, Ana Pardo; Zamorano, José L.; Mehra, Mandeep R.; Butler, Javed; Riess, Hanno; Coats, Andrew J.S.; Anker, Stefan D.
Abstract: We present the hypothesis that advanced stage cancer is also a heart failure syndrome. It can develop independently of or in addition to cardiotoxic effects of anti‐cancer therapies. This includes an increased risk of ventricular arrhythmias. We suggest the pathophysiologic link for these developments includes generalized muscle wasting (i.e. sarcopenia) due to tissue homeostasis changes leading to cardiac wasting associated cardiomyopathy. Cardiac wasting with thinning of the ventricular wall increases ventricular wall stress, even in the absence of ventricular dilatation. In addition, arrhythmias may be facilitated by cellular wasting processes affecting structure and function of electrical cells and conduction pathways. We submit that in some patients with advanced cancer (but not terminal cancer), heart failure therapy or defibrillators may be relevant treatment options. The key points in selecting patients for such therapies may be the predicted life expectancy, quality of life at intervention time, symptomatic burden, and consequences for further anti‐cancer therapies. The cause of death in advanced cancer is difficult to ascertain and consensus on event definitions in cancer is not established yet. Clinical investigations on this are called for. Broader ethical considerations must be taken into account when aiming to target cardiovascular problems in cancer patients. We suggest that focused attention to evaluating cardiac wasting and arrhythmias in cancer will herald a further evolution in the rapidly expanding field of cardio‐oncology.